Ovine induced pluripotent stem cells are resistant to reprogramming after nuclear transfer - German, Sergio D.; Campbell, Keith H.S.; Thornton, Elisabeth; McLachlan, Gerry; Sweetman, Dylan; Alberio, Ramiro (Mary Ann Liebert, 2015)
Induced pluripotent stem cells (iPSCs) share similar characteristics of indefinite in vitro growth with embryonic stem cells (ESCs) and may therefore serve as a useful tool for the targeted genetic modification of farm animals via nuclear transfer (NT). Derivation of stable ESC lines from farm animals has not been possible, therefore, it is important to determine whether iPSCs can be used as substitutes for ESCs in generating genetically modified cloned farm animals. We generated ovine iPSCs by conventional retroviral transduction using the four Yamanaka factors. These cells were basic fibroblast growth factor (bFGF)- and activin A-dependent, showed persistent expression of the transgenes, acquired chromosomal abnormalities, and failed to activate endogenous NANOG. Nonetheless, iPSCs could differentiate into the three somatic germ layers in vitro. Because cloning of farm animals is best achieved with diploid cells (G1/G0), we synchronized the iPSCs in G1 prior to NT. Despite the cell cycle synchronization, preimplantation development of iPSC-NT embryos was lower than with somatic cells (2% vs. 10% blastocysts, p<0.01). Furthermore, analysis of the blastocysts produced demonstrated persistent expression of the transgenes, aberrant expression of endogenous SOX2, and a failure to activate NANOG consistently. In contrast, gene expression in blastocysts produced with the parental fetal fibroblasts was similar to those generated by in vitro fertilization. Taken together, our data suggest that the persistent expression of the exogenous factors and the acquisition of chromosomal abnormalities are incompatible with normal development of NT embryos produced with iPSCs.